Cardiometabolic Health in Obese Adolescents Is Related to Length of Obesity Exposure: A Pilot Study - Zamrazilová, Hana; Weiss, Ram; Hainer, Vojtěch; Aldhoon-Hainerová, Irena (The Journal of clinical endocrinology and metabolism, 2016)
CONTEXT: Metabolically healthy obesity (MHO) is found in a subset of obese individuals. OBJECTIVE: This study sought to examine possible determinants of MHO related to the length of exposure to obesity, lifestyle factors, and dietary intake in adolescent boys. DESIGN: This was a cross-sectional Childhood Obesity Prevalence And Treatment study. Participants and Main Measures: Of 313 boys age 13.0-17.9 years with a body mass index (BMI) ≥ 97th percentile for age, two study cohorts were established based on two definitions of metabolically unhealthy obesity (MUO). Cohort 1 included 18 boys with at least three risk factors (hypertension, dyslipidemia, dysglycemia) who were matched for age, weight, height, and BMI with 18 boys with MHO. Cohort 2 included 35 boys with at least two risk factors who were compared with 31 boys with MHO. MHO was defined by the absence of cardiometabolic risk factors (excluding waist). Data on lifestyle factors and BMI growth trajectories were compared (MHO vs MUO). RESULTS: Boys with MUO (Cohort 1) presented with an earlier onset (4.3 vs 9.1 y; P = .005) and a longer duration of obesity (11.2 vs 6.4 y; P = .003) compared with those with MHO in both group comparisons using different MUO definitions. We found an overall trend toward higher BMI z scores (significant from 3-7 y; P < .001) in metabolically unhealthy compared with their healthy counterparts (Cohort 1). Boys with MHO had higher carbohydrate intake (P < .001). No additional determinants of MHO were observed. CONCLUSIONS: Increased cardiometabolic risk in boys is related to an earlier onset and a longer duration of obesity.
Keywords: metabolicky zdravá obezita; obezita dětí a dospívajících; věk při počátku nemoci; Prevalence; průřezové studie; Life Style; životní styl; Adolescent; Time Factors; časové faktory; lidé; Pilot Projects; pilotní projekty; studie případů a kontrol; metabolické nemoci; Risk Factors; prevalence; Cross-Sectional Studies; Male; Cardiovascular Diseases; Case-Control Studies; Metabolic Diseases; rizikové faktory; kardiovaskulární nemoci; Obesity, Metabolically Benign; Age of Onset; mužské pohlaví; mladiství; Pediatric Obesity; Humans